Biophysical and biochemical characterization of active secondary metabolites from Aspergillus allahabadii. (May 2017) - Rajamanikyam, Maheshwari; Gade, Sriramya; Vadlapudi, Varahalarao; Parvathaneni, Sai Prathima; Koude, Dhevendar; Kumar Dommati, Anand; Kumar Tiwari, Ashok; Misra, Sunil; Sripadi, Prabhakar; Amanchy, Ramars; Upadhyayula, Suryanarayana Murty
Graphical abstract: Highlights: Identification of bioactive secondary metabolites from A. allahabadii using 'activity guided fractionation' strategy. Anti-bacterial secondary metabolites have been isolated from crude extracts. Isolated compounds identified as pyrone derivatives: Maltol and Kojic Acid. These pyrone derivatives have potent anti-microbial, anti-oxidant, mosquito larvicidal and anti-diabetic activities. Abstract: Fungal secondary metabolites are a diverse group of natural chemical products with physiological relevance. We aimed to identify bioactive secondary metabolites from Aspergillus allahabadii . We used "activity-guided fractionation" strategy for the isolation of secondary metabolites. Crude extracts showed good antibacterial activity. Two antibacterial secondary metabolites have been isolated from the crude extract. Chemical characterization of these compounds was performed using biophysical techniques (FT-IR, NMR, and mass spectrometry). Structural characterization confirmed these to be pyrone derivatives: 3-hydroxy 2-methyl 4-pyrone and 5-hydroxy-2-(hydroxymethyl)-4H-pyrone. These bioactive pyrone derivatives have been identified as maltol and kojic acid. From our initial observations, we infer that these pyrone derivatives have potent antimicrobial, antioxidant, antidiabetic, and mosquito larvicidal activities and no cytotoxicity. These compounds could have potential therapeutic and biomedical applications, but further mechanistic studies using animal models are very much necessary.